On a Kantorovich Variant of (p, q)-Szász-Mirakjan Operators. (3rd February 2016) - Mursaleen, M.; Alotaibi, Abdullah; Ansari, Khursheed J.
Abstract : We propose a Kantorovich variant of ( p, q ) -analogue of Szász-Mirakjan operators. We establish the moments of the operators with the help of a recurrence relation that we have derived and then prove the basic convergence theorem. Next, the local approximation and weighted approximation properties of these new operators in terms of modulus of continuity are studied.